Review article: prevention, diagnosis and management of COVID‐19 in the IBD patient. Issue 1 (26th May 2020) - Al‐Ani, Aysha H.; Prentice, Ralley E.; Rentsch, Clarissa A.; Johnson, Doug; Ardalan, Zaid; Heerasing, Neel; Garg, Mayur; Campbell, Sian; Sasadeusz, Joe; Macrae, Finlay A.; Ng, Siew C.; Rubin, David T.; et al.
Summary: Background: The current COVID‐19 pandemic, caused by SARS‐CoV‐2, has emerged as a public health emergency. All nations are seriously challenged as the virus spreads rapidly across the globe with no regard for borders. The primary management of IBD involves treating uncontrolled inflammation with most patients requiring immune‐based therapies. However, these therapies may weaken the immune system and potentially place IBD patients at increased risk of infections and infectious complications including those from COVID‐19. Aim: To summarise the scale of the COVID‐19 pandemic, review unique concerns regarding IBD management and infection risk during the pandemic and assess COVID‐19 management options and drug interactions in the IBD population. Methods: A literature review on IBD, SARS‐CoV‐2 and COVID‐19 was undertaken and relevant literature was summarised and critically examined. Results: IBD patients do not appear to be more susceptible to SARS‐CoV‐2 infection and there is no evidence of an association between IBD therapies and increased risk of COVID‐19. IBD medication adherence should be encouraged to prevent disease flare but where possible high‐dose systemic corticosteroids should be avoided. Patients should exercise social distancing, optimise co‐morbidities and be up to date with influenza and pneumococcal vaccines. If a patient develops COVID‐19, immune suppressing medications should be withheld until infection resolution and if trial medications for COVID‐19 are being considered, potential drug interactions should be checked. Conclusions: IBD patient management presents a challenge in the current COVID‐19 pandemic. The primary focus should remain on keeping bowel inflammation controlled and encouraging medication adherence.